ANALISIS UPAYA MENINGKATKAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA YAYASAN NURUL HIDAYAH KALAM HIKMAH SAWANGAN DEPOK - Bahrul Lutfi Pratama; Syarifah Ida Farida (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the efforts made to improve work discipline and employee performance at the Nurul Hidayah Kalam Hikmah Foundation. One of the foundations that is experiencing challenges in improving employee discipline is the Nurul Hidayah Kalam Hikmah Foundation on Jln.H.Saenan Rt 04\09 Kel. District Surgery Sawangan, Depok City. This foundation operates in the social and educational sectors, with the aim of providing the best service to the community. However, in carrying out its activities, this foundation often faces obstacles in increasing employee discipline, which has an impact on overall organizational performance. This research method uses qualitative methods. Qualitative research emphasizes meaning rather than generalization. Data collection techniques are the most important step in research, because the main aim of research is to obtain data. Data collection can be done in various settings, various sources, and various ways. The results of interviews and observations can be concluded by the author that in any situation when the leader lacks approach to employees and lacks comfort in the work environment, this also influences efforts to improve work discipline. Discipline can be interpreted as a condition created by a series of behavior, obedience and order, one of the factors that influencing performance discipline at the Nurul Hidayah Kalam Hikmah Foundation is a lack of motivation from leadership, a lack of approach to employees, rules that do not comply with a lack of rewards for employees, sometimes inappropriate regulations are the cause of lack of employee discipline. In responding to these problems, management has carried out evaluations slowly by providing examples to employees, creating a good environmental atmosphere, making rules, providing motivation to employees and holding internal meetings between employees.